Comparing conformal, arc radiotherapy and helical tomotherapy in craniospinal irradiation planning. (8th September 2014) - Myers, Pamela A.; Mavroidis, Panayiotis; Papanikolaou, Nikos; Stathakis, Sotirios
Abstract : Currently, radiotherapy treatment plan acceptance is based primarily on dosimetric performance measures. However, use of radiobiological analysis to assess benefit in terms of tumor control and harm in terms of injury to normal tissues can be advantageous. For pediatric craniospinal axis irradiation (CSI) patients, in particular, knowing the technique that will optimize the probabilities of benefit versus injury can lead to better long‐term outcomes. Twenty‐four CSI pediatric patients (median age 10) were retrospectively planned with three techniques: three‐dimensional conformal radiation therapy (3D CRT), volumetric‐modulated arc therapy (VMAT), and helical tomotherapy (HT). VMAT plans consisted of one superior and one inferior full arc, and tomotherapy plans were created using a 5.02 cm field width and helical pitch of 0.287. Each plan was normalized to 95% of target volume (whole brain and spinal cord) receiving prescription dose 23.4 Gy in 13 fractions. Using an in‐house MATLAB code and DVH data from each plan, the three techniques were evaluated based on biologically effective uniform dose ( D ¯ ¯ ), the complication‐free tumor control probability ( P + ), and the width of the therapeutically beneficial range. Overall, 3D CRT and VMAT plans had similar values of D ¯ ¯ (24.1 and 24.2 Gy), while HT had a D ¯ ¯ slightly lower (23.6 Gy). The average values of the P + index were 64.6, 67.4, and 56.6% for 3D CRT, VMAT, and HT plans, respectively, with the VMAT plans having a statistically significant increase in P + . Optimal values of D ¯ ¯ were 28.4, 33.0, and 31.9 Gy for 3D CRT, VMAT, and HT plans, respectively. Although P + values that correspond to the initial dose prescription were lower for HT, after optimizing the D ¯ ¯ prescription level, the optimal P + became 94.1, 99.5, and 99.6% for 3D CRT, VMAT, and HT, respectively, with the VMAT and HT plans having statistically significant increases in P + . If the optimal dose level is prescribed using a radiobiological evaluation method, as opposed to a purely dosimetric one, the two IMRT techniques, VMAT and HT, will yield largest overall benefit to CSI patients by maximizing tumor control and limiting normal tissue injury. Using VMAT or HT may provide these pediatric patients with better long‐term outcomes after radiotherapy. PACS number: 87.55.dk